2020
DOI: 10.7150/ijbs.45357
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of SARS-CoV-2 RNA shedding in clinical specimens and clinical characteristics of 10 patients with COVID-19 in Macau

Abstract: As a city famous for tourism, the public healthcare system of Macau SAR has been under great pressure during the outbreak of the Coronavirus Disease 2019 . In this study, we report clinical and microbiological features of ten COVID-19 patients enrolled in the Centro Hospitalar Conde de São Januário (CHCSJ) between January 21 to February 16, 2020. Clinical samples from all patients including nasopharyngeal swab (NPS)/sputum, urine, and feces were collected for serial virus RNA testing by standard qRT-PCR assay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
321
6
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 312 publications
(355 citation statements)
references
References 19 publications
12
321
6
8
Order By: Relevance
“…All studies had information regarding our primary aim of reporting faecal samples for the virus in those with COVID-19. Of these, 16 [7,10,11,[14][15][16][17][18][19]23,24,[26][27][28][29][30] provided information on the duration of these tests after symptom onset and evidence of positive faecal samples after symptom recovery, discharge from the hospital or negative nasopharyngeal RT-PCR. A total of 824 patients were included across the studies and 540 were tested for faecal viral RNA .…”
Section: Resultsmentioning
confidence: 99%
“…All studies had information regarding our primary aim of reporting faecal samples for the virus in those with COVID-19. Of these, 16 [7,10,11,[14][15][16][17][18][19]23,24,[26][27][28][29][30] provided information on the duration of these tests after symptom onset and evidence of positive faecal samples after symptom recovery, discharge from the hospital or negative nasopharyngeal RT-PCR. A total of 824 patients were included across the studies and 540 were tested for faecal viral RNA .…”
Section: Resultsmentioning
confidence: 99%
“…Thus far, most analyses of urine specimens for SARS-CoV-2 have been negative. 2,30,31 One study in China found SARS-CoV-2 RNA in the urine of 4 COVID-19 patients requiring hospitalization out of a total of 58 patients in the cohort. 32 In addition to urine, the virus RNA has been found in blood specimens.…”
Section: Endoscopymentioning
confidence: 99%
“…In addition to blood, SARS-CoV-2 RNA has been found in stool samples. 31,40 It is unknown whether the virus is present in peritoneal fluid. Despite the lack of evidence of transmission of the virus to health care workers during laparoscopy, steps are advised to reduce the risk of aerosolization during release of pneumoperitoneum and diathermy until more information is available.…”
Section: Laparoscopy and Robotics Vs Open Surgerymentioning
confidence: 99%
“…They also compared and contrasted the different HCoVs from a perspective of virus evolution and genome recombination[2]. Lo et al reported their experience on the evaluation of SARS-CoV-2 RNA shedding in clinical specimens and clinical features of all 10 patients in Macau, and recommended the assessment of both fecal and respiratory specimens for enhancing diagnostic sensitivity[3].Because of no specific anti-virus drugs or vaccines are available for the treatment of this sudden and lethal disease, many drugs have been used in the therapy. Yang et al reported that greater than 85% of COVID-19 patients in China have been receiving Traditional Chinese Medicine (TCM) treatment, and presented the clinical evidence showing the beneficial effect of TCM in the treatment of the patients[4].…”
mentioning
confidence: 99%